2006
DOI: 10.1111/j.1600-6143.2006.01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus with Mycophenolate Mofetil (MMF) or Sirolimus vs. Cyclosporine with MMF in Cardiac Transplant Patients: 1-Year Report

Abstract: suggest that the TAC/MMF combination appears to offer more advantages than TAC/SRL or CYA/MMF in cardiac transplant patients, including fewer ≥3A rejections or hemodynamic compromise rejections and an improved side-effect profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
164
2
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(185 citation statements)
references
References 25 publications
12
164
2
5
Order By: Relevance
“…Moreover, the fibrogenic potential of tacrolimus also appears to be lower (210), although these results could not be confirmed in a more recent study (135). In nonrenal solid organ transplantation, there are singleand multicenter studies as well as registry analyses demonstrating the benefit of tacrolimus over cyclosporine with regard to renal function (24, [211][212][213][214], although other studies did not observe this benefit of tacrolimus over cyclosporine (215).…”
Section: Comparison Between Cyclosporine and Tacrolimusmentioning
confidence: 99%
“…Moreover, the fibrogenic potential of tacrolimus also appears to be lower (210), although these results could not be confirmed in a more recent study (135). In nonrenal solid organ transplantation, there are singleand multicenter studies as well as registry analyses demonstrating the benefit of tacrolimus over cyclosporine with regard to renal function (24, [211][212][213][214], although other studies did not observe this benefit of tacrolimus over cyclosporine (215).…”
Section: Comparison Between Cyclosporine and Tacrolimusmentioning
confidence: 99%
“…Some studies have shown higher incidence of infection in diabetic cardiac transplant patients compared to nondiabetic patients [129]. Discrepancies in the results of these studies are attributed to the limitations including defining criteria for the diagnosis of diabetes, therapeutic regimen used for the management of diabetes, target glycemic control and presence of any associated micro or macrovascular complications of diabetes [131,137,138]. Further studies are required to define the therapeutic targets and impact of glycemic control on development and prognosis of CAV.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…There is a high prevalence of hypertension and other metabolic abnormalities in patients with renal dysfunction. CNIs affect the glomerular filtration and are identified as nephrotoxic agents [131]. Ischemic etiology of end stage heart disease prior to transplantation has been associated with increased risk of CAV.…”
Section: Other Non-immunologic Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for conversion from CSA to Tac for 7 patients was to allow optimization of immunosuppression due to recurrent rejection, because previous reports had revealed a superiority of Tac over CSA for treating rejection and graft survival. 25,26) One patient required conversion from CSA to Tac due to reversible posterior leukoencephalopathy, which occurred immediately after transplantation when the patient was treated with CSA. 27) One patient was weaned from calcineurin inhibitors to avoid the risk of developing posttransplant lymphoproliferative disorder; this patient showed an elevation of human Epstein-Barr virus DNA.…”
Section: Patient Characteristics and Surgical Proceduresmentioning
confidence: 99%